An investigation into the attitude and behaviours of ferry passenger towards general waste management. (1st November 2021) - Lau, Yui-yip; Kawasaki, Tomoya; Guan, Jieqi; Not, Christelle
Abstract: The research study empirically investigates ferry passenger's perception and behaviours towards general waste management and recycling. Structural equation modelling and confirmatory factor analysis were used on survey data gathering from 400 ferry passengers in Hong Kong. The exploratory factor analysis recognized four key dimensions of general waste management and five main dimensions of recycling. Results showed that ferry passengers' attitude on general waste management and recycling are closely associated. Promotion on recycling or display of recycle initiative/guideline can stimulate passengers' attitude on recycling, as well as perceived convenience of recycling can improve passengers' attitude on recycling. However, promotion on recycling or display of recycle initiative/guideline and perceived convenience of recycling only slightly improve ferry passengers' attitude on general waste management suggesting each type of waste need to dedicated information to enhance proper disposal habits by passengers. Implications of research findings on waste management in ferry operations improvements and recommendations for waste management development are also provided. Highlights: SEM and CFA were used on survey data gathered from 400 Hong Kong ferry passengers. Ferry passengers' attitude on waste management and recycling are closely associated. Promotion on recycling stimulates passengers' attitude on recycling. Perceived convenience of recycling improves passengers' attitude on recycling. General waste management in ferry operations improvements are urgently demanded.